Oral health behavior and oral health service utilization among cancer patients in China: A multicenter cross-sectional study - An, Ran; Wu, Zitong; Liu, Meizi; Zhao, Yaqin; Chen, Wenfeng (Frontiers in Oncology, 2023)
Purpose: Oral health plays an important role in overall health. But there is scarce information available on oral health behavior and oral health service utilization among cancer patients. This study aimed to evaluate oral health behavior and oral health service utilization among different population groups of cancer patients in China. Methods: A multicenter cross-sectional study in three tertiary hospitals was conducted to explore the oral health behaviors and oral health service utilization of 162 cancer patients in China. Results: We investigated a total of 162 cancer patients, 81 from urban and rural areas, respectively. The participant’s ages ranged from 18 and 82 years, mean age was 44.62 years (SD = 15.72). Overall, cancer patients have poor oral health behaviors and limited oral health service utilization. There were statistically significant differences (p < 0.05) between urban and rural cancer patients in terms of oral health behaviors including brushing methods, the use of fluoride toothpaste, the use of dental floss, dental caries, and bleeding gums while brushing teeth. As for oral health service utilization, there were significant differences (p < 0.05) between urban and rural cancer patients on regular dental cleaning, the reasons for visiting a dental clinic, and whether they took the initiative to learn about oral health. Conclusion The study findings suggest that cancer patients had poor oral health behaviors and limited oral health service utilization, and rural patients perform poorer than their urban counterparts. Oral health education should be provided to cancer patients to improve their oral health behaviors and oral health service utilization.